2006 International Conference on Information Technology: Research and Education 2006
DOI: 10.1109/itre.2006.381541
|View full text |Cite
|
Sign up to set email alerts
|

Internship as an Obligatory Requirement for the Degree of B.Sc. in Electronic and Electrical Engineering

Abstract: Internship is an inseparable part of some curricula such as Medicine, Law, Accounting, Teaching and more disciplines, where internship is a crucial part of the curriculum. This is not the situation when it comes to technological studies such as Electronics. Is there any justification for this?This article reviews ten years experience of implementing internship at more then 130 Hi -Tech. factories and research institutes, as an obligatory requirement for the Bachelor degree in EEE. The paper presents the suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Besides, this has helped many students make learned career decisions as well as helping organizations to find resources with skill-sets to meet their needs easily [2,5]. Studies have indicated that internship course help bridge the industry-academia gap [7].…”
Section: Internship Modelmentioning
confidence: 99%
“…Besides, this has helped many students make learned career decisions as well as helping organizations to find resources with skill-sets to meet their needs easily [2,5]. Studies have indicated that internship course help bridge the industry-academia gap [7].…”
Section: Internship Modelmentioning
confidence: 99%